CD36 maintains the gastric mucosa and associates with gastric disease - Miriam Jacome-Sosa (Nature Portfolio, 2021)
Jacome-Sosa et al. examine gastric function of CD36, reporting that CD36 knockout mice have altered gland organization and exhibit more fibronectin and inflammatory signaling. The authors find mucosal repair is abrogated due to defective epithelial cell renewal and progenitor cell differentiation, due to reduced fatty acid delivery and altered lipid metabolism, and find associations between low CD36 expression and gastric diseases.